EFEKTIVITAS PENGGUNAAN SIMULASI PHET DALAM PEMBELAJARAN ONLINE TERHADAP HASIL BELAJAR SISWA - Mohammad Muhsin Arifin; Srihandono Budi Prastowo; Alex Harijanto (JURNAL PEMBELAJARAN FISIKA, 2022)
This research is a type of descriptive research. This study aims to examine the effectiveness of using PhET simulation in online learning on temperature and heat material based on student learning outcomes. The level of student effectiveness can be known through the results of the Pre-test and Post-test. PhET simulation is a virtual laboratory simulation covering physics, chemistry, mathematics, earth science, and biology. Furthermore, this research was carried out at SMAN 2 Jember from 3 - 6 January 2022 in the even semester of the 2021/2022 academic year. The population in this study were students of class XI IPA SMAN 2 Jember. Prior to sampling, homogeneity test was carried out with the help of the SPSS program. This homogeneity test is used to determine whether the sample data is obtained from a population with homogeneous variance or not. Data on the effectiveness of using PhET simulation in online learning on temperature and heat materials were obtained from test results. it is known that the N-gain score obtained is 0.669. So it can be concluded that the effectiveness of using PhET simulation in online learning on temperature and heat material is in the medium category. Student learning outcomes also increased compared to before using the PhET simulation. Meanwhile, students admitted that they were enthusiastic and not bored so that it was easier for students to understand the material taught by the teacher. Keywords: effectiveness, PhET simulation, student outcomes, pretest-postest.